Remodeling of keratin-coupled cell adhesion complexes. (February 2015) - Osmani, Naël; Labouesse, Michel
Abstract : Epithelial cells constitute the main barrier between the inside and outside of organs, acting as gatekeepers of their structure and integrity. Hemidesmosomes and desmosomes are respectively cell–matrix and cell–cell adhesions coupled to the intermediate filament cytoskeleton. These adhesions ensure mechanical integrity of the epithelial barrier. Although desmosomes and hemidesmosomes are essential in maintaining strong cell–cell and cell–matrix adhesions, there is an emerging view that they should be remodeled in order to maintain epithelial homeostasis. Here we review the adhesion properties of desmosomes and hemidesmosomes, as well as the mechanisms driving their remodeling. We also discuss recent data suggesting that keratin-coupled adhesion complexes can sense the biomechanical cellular environment and participate in the cellular response to such external cues.